Low-intensity ultrasound attenuates paw edema formation and decreases vascular permeability induced by carrageenan injection in rats - Kil Hwan Kim; Hyeon-Woo Im; Mrigendra Bir Karmacharya; Sejong Kim; Byoung-Hyun Min; So Ra Park; Byung Hyune Choi (BMC, 2020)
Abstract Background Therapeutic potential of low-intensity ultrasound (LIUS) has become evident in various musculoskeletal diseases. We have previously shown that LIUS has an inhibitory effect on local edema in various diseases including the arthritis and brain injury. In this study, we examined whether LIUS can attenuate paw edema formation vis-à-vis vascular permeability and inflammation in rats induced by carrageenan. LIUS with a frequency of 1 MHz and the intensities of 50, 100, or 200 mW/cm2 were exposed on rat paws for 10 min immediately after carrageenan injection. Results Carrageenan injection induced paw edema which was peaked at 6 h and gradually decreased nearly to the initial baseline value after 72 h. LIUS showed a significant reduction of paw edema formation at 2 and 6 h at all intensities tested. The highest reduction was observed at the intensity of 50 mW/cm2. Histological analyses confirmed that LIUS clearly decreased the carrageenan-induced swelling of interstitial space under the paw skin and infiltration of polymorphonuclear leukocytes. Moreover, Evans Blue extravasation analyses exhibited a significant decreases of vascular permeability by LIUS. Finally, immunohistochemical staining showed that expression of pro-inflammatory proteins, namely, inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) induced by carrageenan injection was reduced back to the normal level after LIUS stimulation. Conclusions These results provide a new supporting evidence for LIUS as a therapeutic alternative for the treatment of edema in inflammatory diseases such as cellulitis.